DEZBATERI INTER-CONFESIONALE ÎN ROMÂNIA INTERBELICĂ. STUDIU DE CAZ: DEZBATEREA CE TREBUIA SĂ AIBĂ LOC ÎNTRE PASTORUL ADVENTIST ȘTEFAN DEMETRESCU ȘI PREOTUL PETRE CHIRICUȚĂ LA FUNDAȚIA UNIVERSITARĂ CAROL I ÎN ANUL 1931 (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Inter-confessional Debates in Interwar Romania. Case study: The Debate that was to take place between Adventist Pastor Stefan Demetrescu and Priest Petre Chiricuta at the Carol I University Foundation in 1931.The inter-war time in Romanian society was the most effervescent period in terms of debates on religious issues in all our known history. In the newspapers of the times, in the Parliament’s rostrum or in usual meetings, religion was regular topic of discussion and stirred up very strong emotions. But beyond what we could glean from the extremely harsh words used, or even in persecutions’ accounts, we cannot fail to notice an amazing thirst for knowledge. A very good example of this desire for mutual knowledge is the “contradictory public discussion” proposed by Orthodox priest Petre Chiricuța of the “Hagiu” Church in Bucharest to Adventist pastor Stefan Demetrescu on the topic of the Second Coming of Christ, discussion that was to take place at the Fundația Universitară Carol I in March 1931. Even if the Patriarchy cancelled the meeting at the last moment, the preparation of the event and the reactions sparked by its cancellation help us to see how religious debate was present at all levels in Romanian society during that period.